Acoustic holographic assembly of cell-dense tissue constructs - Shi, Minghui; Fischer, Peer; Melde, Kai (Biofabrication, 2025)
Tissue engineering aims to develop tissue constructs as models or substitutes for native tissues. For organ-level biological studies and regenerative medicine applications, it is essential to fabricate tissue constructs with physiologically relevant cell densities (on the order of 10 million to 1 billion cells·ml−1), large size (centimeter scale and larger), and a controllable geometry to guide tissue maturation. State-of-the-art biofabrication methods, however, struggle to simultaneously meet all of these demands. The recently proposed acoustic holographic assembly (AHA) method shows promise, as it is compatible with culture media and enables the contactless, label-free, and volumetric assembly of biological cells in a predefined geometry within few minutes. Here we present an AHA biofabrication scheme designated for fabricating cell-dense, centimeter-scale, and arbitrarily-shaped tissue constructs using a compact benchtop instrument compatible with a biolab environment. We demonstrate the assembly of C2C12 myoblasts in gelatin methacryloyl (GelMA) into large and asymmetric branch-shaped constructs, which are rapidly formed with an average cell density of 40 million cells·ml−1 and a local density of up to 260 million cells·ml−1. Featuring a high viability of 90.5 ± 4.3%, the assembled cell constructs are observed to grow within the GelMA hydrogel under perfusion over five days. Further, we show how AHA can—in a single step—assemble cells into layered and three-dimensional geometries inside standard cell culture labware. It can therefore help obtain engineered tissue constructs with structural and functional characteristics seen in more complex native tissues.